Aortic Valve Reconstruction with Ozaki Technique - Ricciardi,Gabriella (2022)
Abstract Modern bioprostheses offer a complete and definitive solution to elderly patients who need aortic valve surgery. Nonetheless, the scenario is more demanding when dealing with younger and less fragile patients. In this setting, any prosthetic aortic valve replacement can provide only a suboptimal solution and its related issues have not been fixed yet. The answer to the needs of this special population is the enhancement and refinement of the surgical technique. The Ozaki technique relies on custom-tailored autologous aortic cusps individually sutured in the aortic position. This approach has been showing optimal results if performed after a dedicated training period.